Crystalline Maculopathy Secondary to Retinal Tear Without Detachment. (September 2021) - Tsimchi, Imanouel M.; Dayani, Pouya N.; Boyer, David S.; Roe, Richard H.
Purpose: Crystalline maculopathy secondary to chronic retinal detachment (RD) has previously been described. This article proposes a novel mechanism to explain crystalline formation in the absence of RD. Methods: Two patients, who were referred for routine examination, were found to have a crystalline maculopathy in the setting of an asymptomatic, chronic-appearing, peripheral retinal tear. Fundoscopy and optical coherence tomography were used to assess the crystals and tear. No specimens were obtained. Results: We describe 2 cases of a crystalline maculopathy secondary to an asymptomatic peripheral retinal tear. We hypothesized macrophage ingestion of photoreceptor segments emanating from the tear may have contributed to macular crystalline deposition. Conclusions: Because crystalline maculopathy can present in the setting of RD, there may be a shared pathogenesis between the 2 conditions.